(untitled) (Journal of Medical & Health Sciences Review, 2025)
Wheat (Triticum aestivum L.) is the most valuable cereal crop all around the world. Wheat crop needs proper nutrition for its stable growth and better yield. Potassium is one of the most important plant nutrient used for enhancing the wheat production and quality determination. This study was aimed to access the wheat growth and yield influenced by potassium and prevailing temperature under Randomized Complete Block Design (RCBD) with three replicates. The variety evaluated in this study was Punjab 2011 and eight treatments were applied as concentrations; T1= Control (No potash fertilizer application); T2= Potassium 60 kg/ha at sowing; T3= T2 + 2% KNO3 spray at booting; T4= T2 + 2% KNO3 spray at grain filling; T5= T2 + 2% KNO3 spray at booting and grain filling; T6= 1/2T2 + 1/2 dose at booting; T7= 1/2T2 + 1/2 dose at grain filling and T8= 1/3 T2 + 1/3 dose at booting + 1/3 dose at grain filling were applied. Fertilizer 115,85 N.P Kg/ha was applied during seed bed preparation. Biochemical plant analyses were carried under the influence of potassium concentration. The recorded data was analyzed by analysis of one way ANOVA. The results revealed that potassium contents in plants had a significant effect on physiolochemical attributes. Results shows that increase in plant height (cm),crop growth rate (gm-2 day-1), fertile tillers per plant, peduncle length (cm), spike length (cm), flag leaf area (cm2), number of spikelets per spike, grains per spike, thousand grain weight (g), grain yield (kgha-1), biological yield (kg ha-1), harvest index(%), chlorophyl content (mg/g), K concentration, potassium uptake (mg) and Potassium utilization efficiency (g mg-1 K) in plant under prevailing temperature. This study will be helpful for improving the efficacy of crop minerals for growth and yields performance.